A study on the characteristics of copper and copper oxide-based antifouling coatings / Leeana Ismail - Leeana, Ismail (2016)

(untitled)
Coating is the easiest and cheapest method to prevent corrosion. Every country spends enormous money due to the adverse effect of corrosion. Marine industry is facing lot of issues because of corrosion and biofouling problems. There are restrictions to use harmful biocides in antifouling coatings for boats, yachts and ships. In the market, antifouling coatings have been developed using more than 50 wt% of biocide loading. In this work, an attempt was made to reduce the usage of biocide to protect the ocean environment and production cost. In this work, polyester-epoxy resins have been used as the binder to formulate the coating system. The developed coating systems were analysed to evaluate physical, mechanical, structural, thermal and electrochemical properties. The anticorrosion property was examined by electrochemical impedance spectroscopy. The variation of coating resistance, Rc was calculated by analyzing the Bode plot from the impedance data obtained. From FTIR and DSC studies, the formation of crosslinking between the resins was explained. From the performance analyses, the binder system consisting of 90 wt% polyester and 10 wt% epoxy has shown better performance compared to other compositions. It has been selected to develop antifouling coatings. Copper and copper oxides were added as biocide in the antifouling coating system. The optimum pigment volume concentrations of the biocides were found. The best coating resistance, Rc for both copper and copper oxide binder system was found to be in the order of 108 ohm at the end of 30 days of exposure in artificial seawater. Antifouling property of this developed coatings depend on the leaching of the biocide from the coatings. The leaching has been measured by immersing the coated panels in different electrolyte solutions. The electrolyte samples were tested by ICP-OES. The metal concentration in different types of electrolytes reveals that the amount of leaching is greater for the seawater as compared to the distilled water and artificial seawater. The real-time seawater exposure test was carried iv at two locations such as Lumut, Perak and Penang Island in Malaysia. The copper oxide based antifouling coating system showed the best performance in real exposure in seawater since the adhesion of the coating to the steel plates was very good. The microorganism growth on the coated panels was prevented by the leaching of biocide. It has been confirmed by SEM micrographs which were free of microorganism on the surface. From the results it was found that 25 % PVC of copper based antifouling coating and 25 % PVC of copper oxide based antifouling coating showed better performance. Booster biocide (diuron) was added from 1wt. % to 5 wt.% into the two best antifouling coating systems to study the effect of diuron on the antifouling properties. SEM micrographs revealed that the performance of the copper oxide-diuron antifouling coating system was better than the copper oxide antifouling coating system.